Materials of the Third Conference “The Constitution of Russia: Yesterday, Today, Tomorrow” (St. Petersburg, December 9–10, 2019) - Article Editorial (Теоретическая и прикладная юриспруденция)
This material is devoted to a review of expert speeches at the Conference “The Constitution of Russia: Yesterday, Today, Tomorrow”, held in St. Petersburg on December 9–10, 2019. The problems of modern federalism, human rights and freedoms, and their protection by the state and local self-government were discussed at the conference. The experts analyzed the origins and causes of the existing state structure in the Russian Federation, its features and possible development paths; problems of human rights and freedoms in Russia and in other states, as well as the current state of local self-government in Russia, trends in its preservation, expansion and bringing into line with modern requirements of social development in the context of globalization.